The Factors of Using WhatsApp Application in Education Management in Public University: Conceptual Paper - Balasundran, Komathy; Yunus, Jamal @ Nordin; Pandian, Vickneswari; Pandi, Deebamalar (Management Research Journal, 2021)
WhatsApp is a popular platform especially for communication in organizations. It has 1.5 billion users around the world. Although there has been an increase in the number of studies looking at the use of WhatsApp application in various formal settings, its use in education management research is still poorly studied. Therefore, we propose this conceptual paper to be studied. The purpose of this conceptual paper is to review the factors and their relationship with using WhatsApp application in education management in public university. This conceptual paper explores the introduction, literature review, and research methodology. Apart from that, this conceptual paper also discusses the relationship between the factors with the WhatsApp application in education management in public university. The factors focused on are performance expectancy, effort expectancy, social influence, and facilitating condition. The study employs the quantitative method based on survey design. The study population consisted of public university administration staff and lecturers from all over Malaysia. Accordingly, this conceptual paper proposes descriptive and inferential statistics to analyze the data of this study. Statistical Package for Social Science (SPSS) program suggested analyzing the data. Descriptive analysis will be used to measure the level of using WhatsApp application in education management in public university by involving mean, percentage, and standard deviation. Meanwhile, inference statistics will use Pearson Correlation Coefficient to see the relationship between the factors and using WhatsApp application in education management in public university.